2017
DOI: 10.1093/ageing/afx133
|View full text |Cite
|
Sign up to set email alerts
|

Development of an international undergraduate curriculum for delirium using a modified delphi process

Abstract: this Delphi process enabled an international group of experts from a broad range of specialties, to reach consensus agreement on the components of an undergraduate curriculum for delirium. The curriculum represents an important step in the development of delirium education within medical training. Despite competing demands of increasingly crowded undergraduate curricula, delirium, given its relevance to 21st century healthcare, must be prioritised. We call on Medical Schools to consider integrating this deliri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Educational interventions are thought to be most effective when formal teaching is interactive and allows learners opportunities to reflect throughout, and therefore translate theory into their practice [16]. Furthermore, in relation to curriculum design, a modified Delphi process conducted with delirium experts recommended patient involvement in the production and design of any medical educational intervention about delirium [37]. The present study demonstrated a novel approach to undergraduate nursing delirium education through the coproduction of the educational intervention.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Educational interventions are thought to be most effective when formal teaching is interactive and allows learners opportunities to reflect throughout, and therefore translate theory into their practice [16]. Furthermore, in relation to curriculum design, a modified Delphi process conducted with delirium experts recommended patient involvement in the production and design of any medical educational intervention about delirium [37]. The present study demonstrated a novel approach to undergraduate nursing delirium education through the coproduction of the educational intervention.…”
Section: Discussionmentioning
confidence: 86%
“…With regards to healthcare student education, there is limited evidence examining delirium education for undergraduate nursing students. However, research conducted with medical students highlights the importance of tailored delirium education and the positive impact this can have with trainee doctors [37][38][39][40]. In a recent UK study about delirium in undergraduate medical education, it was highlighted that 58% (n = 18) of medical schools in the UK had at least one learning outcome mapped to delirium yet only 4 of these medical schools evaluated their delirium education [38].…”
Section: Discussionmentioning
confidence: 99%
“…There have been similar studies that used the Delphi method to develop curriculums for undergraduate medical education. For example, Kizawa et al developed a (12). However, to the best of our knowledge, in this report we have described the first consensus curriculum for undergraduate diabetes education.…”
Section: Discussionmentioning
confidence: 91%
“…Definitions of consensus vary widely and are poorly reported in the literature. As such, there is limited guidance on how consensus is defined (9,12). Given that there is no set definition for consensus, for this phase, we elected to analyze the results based on 2 methods and then compare and combine them.…”
Section: Delphi Data Analysesdsecond Roundmentioning
confidence: 99%
“…In recent years, researchers have identified persistent gaps in delirium education for healthcare professionals, which has led to suboptimal delirium care [1][2][3][4][5][6][7]. Delirium is an acute neuropsychiatric syndrome characterized by altered attention, awareness, and cognition.…”
Section: Deliriummentioning
confidence: 99%